Investigating bioink hydrogels for 3D bioprinting to reconstitute glioblastoma microenvironment - Wei, Leong Shye (2025)
Glioblastoma, the most aggressive glioma subtype, presents significant challenges due to drug resistance, resulting in frequent recurrence and progression. Traditional two-dimensional (2D) cell cultures often fail to replicate accurately the complex tumor microenvironment and cellular interactions found in vivo, thereby limiting their ability to predict drug response reliably. Addressing this issue, three-dimensional (3D) bioprinting emerges as a modern approach for constructing glioblastoma models, vital for preclinical drug testing. This project aims to fabricate a glioblastoma microenvironment using 3D bioprinting and hydrogels. Various hydrogel compositions; alginate (ALG), a combination of alginate and chitosan (ALG-CHI), and a blend of alginate, chitosan, and hyaluronic acid (ALG-CHI-HA) — were formulated. The physical properties and cell-matrix interactions of these bioink groups (ALG, ALG-CHI, and ALG-CHI-HA) were assessed. Notably, hydrogels composed of 4% ALG, 4%:0.25% ALG-CHI, and 4%:0.25%:0.25% ALG-CHI-HA, when pre-crosslinked with CaCl₂ at the concentration of 0.102 M, they exhibited the most consistent and stable bioprinting results, highlighting the importance of evaluating different bioink compositions and crosslinking parameters to achieve the desired printing outcomes. Furthermore, the study investigated the impact of bioprinting parameters, such as speed and pressure on the quality of the printed constructs. Optimal bioprinting conditions were identified with a printing speed of 8 mm/s and printing pressure of 10 kPa, ensuring precise deposition of bioink materials and maintenance of structural integrity. Porosity assessments demonstrated varying trends over time. ALG hydrogels maintained stable porosity (n.s) after one week of DMEM incubation, whereas ALG-CHI (p<0.05) and ALG-CHI-HA (p<0.001) showed significant decreases in porosity from day 0 to day 7. Swelling ratios remained relatively stable for all bioink groups throughout the 21-day incubation period, ranging between 10.84-14.58. Cell viability assessments revealed distinct trends: ALG demonstrated an initial increase from day 1 to 14, followed by a decrease at day 21 (p<0.001). Conversely, ALG-CHI showed increased in cell viability at day 21 (p<0.05), and ALG-CHI-HA exhibited delayed but significant increased viability between days 7 and 21 (p<0.01). ALG-CHI and ALG-CHI-HA formulations sustained viability over time, suggesting potential for supporting long-term cell growth and proliferation. SEM and histological (H&E) analyses provided valuable visual confirmation into the cellular morphology and organisation within the bioprinted constructs. In conclusion, the bioprinted hydrogels from all groups demonstrated persistent stability and structural integrity throughout. Among the different formulations, ALG-CHI supported higher viability of glioblastoma cells with formation of tumour microenvironment. ALG-CHI-HA also showed similar trend and performance. Hence, ALG-CHI and ALG-CHI-HA are suitable to be used for long-term 3D cell cultures.